A survey on knowledge, attitude and confidence level of adult cardiopulmonary resuscitation among medical officers in health clinics in Kelantan - Baherin, Muhammad Faiz (2015)
Introduction Medical officers are defined as those who have already completed a two-year internship in hospital settings. They will be posted to any government health facilities including health clinics. Health clinics are considered out-of-hospital health facilities. Based on recent statistics, out-of-hospital cardiac arrests survival rates were very low as compared to in-hospital survival rates. Medical officers working in health clinics have long left the hospital settings. Are their knowledge, attitude and confidence level sufficient enough to deal with these cases of cardiac arrest? The aim of this study is to determine the level of knowledge, attitude and confidence of medical officers in health clinics in Kelantan and the factors associated with it. Methodology This was a cross-sectional study using simple random sampling. To validate and test the reliability of the questionnaire, a pre-test was previously done. All medical officers in health clinics in Kelantan were involved in this study. The questionnaire were posted to their workplace and then collected in a period of a few months. The data was entered and analyzed by SPSS software version no 22. Results A total of 75 medical officers were involved in the study. The average age was 30.0 years. 73.4% had practiced medicine for more than two years. 58.7% of them had attended more than 5 cardiac arrest cases and 54.7% of them had last performed CPR for more than 12 months. 98.7% had attended BLS courses. 28% out of them had never attended ACLS Courses. 40% of the subjects achieved good knowledge scoring. 100% of these subjects had positive attitude towards adult CPR. In the confidence domain, 53.3% of the subjects had poor confidence in dealing with resuscitation. 60% was not confident to perform endotracheal intubation, 49.3% was not confident to perform defibrillation, 48% was not confident in using resuscitation drugs and 41.3% was not confident to be the team leader in resuscitation. ACLS training was the most important factor that improved their confidence level in adult cardiopulmonary resuscitation. Conclusion Knowledge of adult CPR among medical officers in health clinics in Kelantan was only average but all of them had positive attitude. The majority had low confidence level. From the study, it was revealed that ACLS training improved both knowledge and confidence level of the doctors. The researcher’s recommendation includes integration of life support courses in medical school’s syllabus as well as frequent recertification of the courses for everyone. Better knowledge, attitude and confidence level in cardiopulmonary resuscitation would lead to a better healthcare system in Malaysia.